Strategi Peningkatan Minat Baca Siswa MTs Mujahidin Melalui Pemanfaatan Teknologi Informasi di Perpustakaan - Deni Mulyadi; Herman, Maman (Journal of Elementary Education: Strategies, Innovations, Curriculum, and Assesment, 2025)
The low interest in reading among students has become a problem faced by MTs Mujahidin. This study aims to identify strategies to increase reading interest among students of MTs Mujahidin through the utilization of information technology in the library. The subjects of this study were all students of MTs Mujahidin, with a sampling technique using proportional stratified random sampling involving 60 students. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. Data analysis was carried out interactively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the utilization of information technology in the library, such as the provision of e-books, internet access, digital library applications, and social media, can increase students' interest in reading. The strategies implemented include: (1) providing adequate information technology facilities, (2) digital literacy training for students and librarians, (3) developing attractive digital content, (4) integrating information technology in learning, and (5) periodic evaluation and development of programs. This research has implications for schools in designing and implementing strategies to increase students' interest in reading based on information technology.